Analisis Daerah Rawan Kecelakaan Jalur Wisata Pantai Selatan Gunungkidul Menggunakan Metode Transport Research Laboratory (TRL) Dan Killed Serious Injured (KSI) (Studi Kasus: Ruas Jalan Baron): Analysis Of Accident Prone Areas Tourism Routes Of Gunung Kidul South Beach Using Transport Research Laboratory (TRL) And Killed Serious Injured (KSI) Methods (Case Study: Baron Roads Section) - Detha Sekar Langit Wahyu Gutama; Galih Rio Prayogi; Yuliati Nengsih (Media Ilmiah Teknik Sipil, 2023)
Accident-prone locations black spot, accident characteristics, and factors that cause accidents. The methods used to identify accident-prone areas are the Transportation Research Laboratory (TRL) and the Killed Seriously Injured (KSI) method. The data needed is traffic accident data in 2016 - 2020 from the Gunungkidul Police and geometric data. Based on the results of the analysis of the emergence of black spots at Km 1 - Km 2, Km 2 - Km 3, Km 3 - Km 4, Km 4 - Km 5, Km 5 -Km 6 and Km 20 - Km 21. Characteristics of traffic accidents that occur on this road segment Jalan Baron Gunungkidul based on accident rate data in 2016-2020, there were 202 accidents from time to time up to 80 accidents during the day (12:00-18:00), depending on the type of collision a total of 52 head-on collisions, according to the type of vehicle is up to 284 vehicles with motorized vehicles, based on road type has up to 140 accidents with straight road type. Factors causing accidents on Jalan Baron are caused by humans, this one is caused by drivers who are less skilled in controlling vehicles and do not understand the meaning of traffic signs